Genetic evidence for direct sensing of phenolic compounds by the VirA protein of Agrobacterium tumefaciens. - Lee, Y W (1995)
The virulence (vir) genes of Agrobacterium tumefaciens are induced by low-molecular-weight phenolic compounds and monosaccharides through a two-component regulatory system consisting of the VirA and VirG proteins. However, it is not clear how the phenolic compounds are sensed by the VirA/VirG system. We tested the vir-inducing abilities of 15 different phenolic compounds using four wild-type strains of A. tumefaciens--KU12, C58, A6, and Bo542. We analyzed the relationship between structures of the phenolic compounds and levels of vir gene expression in these strains. In strain KU12, vir genes were not induced by phenolic compounds containing 4'-hydroxy, 3'-methoxy, and 5'-methoxy groups, such as acetosyringone, which strongly induced vir genes of the other three strains. On the other hand, vir genes of strain KU12 were induced by phenolic compounds containing only a 4'-hydroxy group, such as 4-hydroxyacetophenone, which did not induce vir genes of the other three strains. The vir genes of strains KU12, A6, and Bo542 were all induced by phenolic compounds containing 4'-hydroxy and 3'-methoxy groups, such as acetovanillone. By transferring different Ti plasmids into isogenic chromosomal backgrounds, we showed that the phenolic-sensing determinant is associated with Ti plasmid. Subcloning of Ti plasmid indicates that the virA locus determines which phenolic compounds can function as vir gene inducers. These results suggest that the VirA protein directly senses the phenolic compounds for vir gene activation.